PTEN inhibition attenuates endothelial cell apoptosis in coronary heart disease via modulating the AMPK–CREB–Mfn2‐mitophagy signaling pathway. Issue 5 (25th October 2019) - Li, Pei; Wang, Jing; Zhao, Xia; Ru, Jing; Tian, Tian; An, Yun; Tang, Liying; Bai, Yuzhi
Abstract: Atherosclerosis (AS) is a major pathogenic factor in patients with cardiovascular diseases, and endothelial dysfunction (ED) plays a primary role in the occurrence and development of AS. In our study, we attempted to evaluate the role of phosphatase and tensin homolog (PTEN) in endothelial cell apoptosis under oxidized low‐density lipoprotein (ox‐LDL) stimulation and identify the associated mechanisms. The results of our study demonstrated that ox‐LDL induced human umbilical vein endothelial cell (HUVEC) death via mitochondrial apoptosis, as evidenced by reduced mitochondrial potential, increased mitochondria permeability transition pore opening, cellular calcium overload, and caspase‐9/‐3 activation. In addition, ox‐LDL also suppressed cellular energy production via downregulating the mitochondrial respiratory complex. Moreover, ox‐LDL impaired HUVECs migration. Western blot analysis showed that PTEN expression was upregulated after exposure to ox‐LDL and knockdown of PTEN could attenuate ox‐LDL‐mediated endothelial cell damage. Furthermore, we found that ox‐LDL impaired mitophagy activity, whereas PTEN deletion could improve mitophagic flux and this effect relied on the activity of the AMP‐activated protein kinase (AMPK)–cAMP‐response element‐binding protein (CREB)–Mitofusin‐2 (Mfn2) axis. When the AMPK–CREB–Mfn2 pathway was inhibited, PTEN deletion‐associated HUVECs protection was significantly reduced, suggesting that the AMPK–CREB–Mfn2‐mitophagy axis is required for PTEN deletion‐mediated endothelial cell survival under ox‐LDL. Taken together, our results indicate that ox‐LDL‐induced endothelial cell damage is associated with PTEN overexpression, and inhibition of PTEN could promote endothelial survival via activating the AMPK–CREB–Mfn2‐mitophagy signaling pathway. Abstract : Taken together, our results indicate that oxidized low‐density lipoprotein (ox‐LDL)‐induced endothelial cell damage is associated with phosphatase and tensin homolog (PTEN) overexpression and inhibition of PTEN could promote endothelial survival via activating the AMP‐activated protein kinase (AMPK)–cAMP‐response element‐binding protein (CREB)–Mitofusin‐2 (Mfn2)‐mitophagy signaling pathway.